Intra-articular lentivirus-mediated gene therapy targeting CRACM1 for the treatment of collagen-induced arthritis - Shuang Liu; Takeshi Kiyoi; Erika Takemasa; Kazutaka Maeyama (Elsevier, 2017)
Abnormal store-operated calcium uptake has been observed in peripheral T lymphocytes of rheumatoid arthritis (RA) patients, and sustained intracellular calcium signalling is known to mediate the functions of many types of immune cells. Thus, it is hypothesized that regulating calcium entry through CRACM1 (the pore-forming subunit of calcium release-activated calcium (CRAC) channels; also known as ORAI1) may be beneficial for the management of RA. Localized CRACM1 knockdown in the joints and draining lymph nodes (DLNs) of mice with collagen-induced arthritis (CIA) was achieved via lentiviral-based delivery of shRNA targeting mouse CRACM1. Consistent with CRACM1 knockdown, calcium influx in synovial cells and the histopathological features of CIA were reduced. These effects were also associated with reduced levels of several notable inflammatory cytokines, such as IL-6, IL-17A, and IFN-γ, in the joints. Additionally, CRACM1-shRNA reduced the number of bone marrow-derived osteoclasts in vitro as well as osteoclasts in CIA joints, which was associated with reduced RANKL levels in the serum and joints. In summary, inhibiting calcium entry by CRACM1 knockdown suppressed arthritis development and may be therapeutically beneficial for RA patients.